The spiritual ecology of sacred landscapes: Evidence from sacred forests of the Sebat Bête Gurage, Central - South Ethiopia - Abinet Shiferaw; Mamo Hebo; Getachew Senishaw (Cogent Social Sciences)
Sacred landscapes are texts of sustainable human-ecological relationships with strong senses of spirituality. This article explores the sacred and dynamic aspects of the Sebat Bête Gurage landscapes using ethnographic research design. Furthermore, to grasp elements of sacred environments and their dynamics, a spiritual ecology perspective was used. The data was based on ethnographic sources, with original data gathered through in-depth interviews, focus group discussions, observations, and an inventory of sacred sites. And data from sacred forest facts and people’s experiences were examined using ethnographic data analysis approaches such as thematization and meaning constructions generated from primary data sources through data triangulation. The study examines indigenous religious aspects and sacredness; the characteristics and spiritual dimensions of sacred forests; the nature of engagements and benefits obtained from sacred forests; governance practices and dynamics aspects of sacred forests; and the implications of dynamics on human-ecology interaction sustainability among the Gurage. The study’s findings also revealed the multi-functionalities of sacred forests for forest-surrounding communities, as well as the importance of managing sustainable nature-culture interactions in the quest for spiritual ecology and sustainable living. The research also portrays the effects of human intrusions on the state of sacred forests and their provisions. The article concludes with a call for concern for multifunctional sacred landscape governance.